Eksplorasi Karakteristik Pembangunan Ekonomi Desa Melalui Unsur-Unsur Budaya Universal di Desa Ngadas Kecamatan Poncokusumo Kabupaten Malang - Endro Pebi Trilaksono (Universitas Negeri Malang, 2015)
Indonesia has a diverse culture where culture is an attempt of a man to maintain their identity. The role of local culture on the characteristics of rural economic development will be explained through the Universal Cultural Elements. The purpose of this study was to determine (1) the role of culture Ngadas Village Poncokusumo Malang on the characteristics of rural economic development, and (2) the characteristics of the village economic development Ngadas Poncokusumo Malang. This study used a qualitative approach, while the type of research is ethnography. Data collected through interviews, observation and documentation covering the cultural and economic development of the village. Results of the study are (1) the cultural community is very influential on the characteristics of rural economic development. (2) Characteristics of the village economic development Ngadas Poncokusumo Malang is Agriculture Rural Area.Keywords: Rural Economic Development, Cultural Elements Universal